Vanguard [videorecording (DVD)] - Tong, Stanley; Tong, Stanley; Tong, Stanley; Cheng, Long, 1954-; Yang, Yang, 1991-; Muqi, Miya, 1987- (Lionsgate, 2021)
The head of a covert security company and his team try to protect a businessman and his family who are targeted by a mercenary organization after an arms deal.